(untitled) (Scientific journal of the Fergana State University, 2023)
Freshly cut cabbage juice is very useful for human health, it contains many useful substances that are easily absorbed by our body, it is used in traditional medicine against various diseases. It is known that scientists have applied various methods to study the antioxidant activity of plant extracts. This article provides information about the antioxidant properties of cabbage juice.